The Expectancy‐Disconfirmation Model and Citizen Satisfaction with Public Services: A Meta‐analysis and an Agenda for Best Practice - Zhang, Jiasheng; Chen, Wenna; Petrovsky, Nicolai; Walker, Richard M. (Public administration review, 2022)
The expectancy‐disconfirmation model has become the predominant approach in explaining citizen satisfaction with public services. It posits that citizens compare the performance of a service against their expectations of that service. Satisfaction occurs if the perceived performance meets or exceeds the expectations. We provide the first meta‐analysis of the empirical evidence on this relationship, and find that the model is supported across studies. However, our meta‐analysis also indicates that research design choices affect the results and that the scope of public services examined is not comprehensive. We make best practice recommendations for future research to improve the measurement of citizen satisfaction.